The Labor Market Gender Gap in Denmark: Sorting Out the Past 30 Years - Yana Gallen; Rune V. Lesner; Rune Majlund Vejlin (Institute of Labor Economics (IZA), 2017)
We document the declining gap between the average earnings of women and men in Denmark from 1980 to 2010. The decline in the earnings gap is driven by increased labor force participation and increases in hours worked by women, and to a smaller extent by a decline in the gender wage gap. The gap has declined least among higher earning women – the average wage of the top 10 percent of female earners is 28-33% lower than the average wage of the top 10 percent of male earners. Women are becoming more educated and are a larger share of the professional labor force than in previous decades, but a substantial wage gap of about 10 percent remains for the youngest cohorts even after controlling for age, education, experience, occupation, and firm choice. Unlike the case of the US, differences in educational attainment, occupational choice, industry, and experience explained about 15 percentage points of the Danish wage gap in 1980, but now these factors explain only about 6 percentage points of the Danish wage gap. In fact, though variation in the wage gap across occupations is substantial, this variation is not correlated with the fraction of the occupation which is female. The data show a great deal of sorting and segregation across industries, occupations, and even firms. However, this sorting does not explain more than half of the wage gap. We conclude that a great deal of the remaining disparity between the wages of women and men is tied to the differential effects of parenthood by gender.
Keywords: J71; J31; 330; gender pay gap; sorting